Emotion and interpersonal relationships: A fruitful dialectic - Καφέτσιος Κωνσταντίνος (Psychology: the Journal of the Hellenic Psychological Society, 2018)
Emotion and relationships are involved in an intricate dialectic. Relational contexts can influence the perception, experience and communication of strong emotion, and conversely, emotion and affective processes within close relationships can influence the quality of the relationship between two persons. The present paper discusses central approaches to emotion in interpersonal relationships from a socio-cognitive, relational and behavioral perspective. Through a critical evaluation of those approaches the importance of focusing on emotional and affective processes in interpersonal interaction is underlined. These processes are suggestive of the interdependent nature of interpersonal interaction in relationships. Research and theory on emotion and affect in interpersonal interaction can provide the basis of a multilevel model that can explain how intrapersonal and relationally situated processes (including factors outside the relationship) can influence emotion in highly interdependent contexts, and conversely, how emotional and affective processes in interpersonal interaction can determine relational schemas.